THE INFLUENCE OF UNDERSTANDING OF ACCOUNTING SYSTEM, GOVERNMENT FINANCIAL MANAGEMENT AND WORK ENVIRONMENT ON PERFORMANCE OF WORK UNITS - Susan Rondonuwu; Agustinus Salle; Paulus K. Allo Layuk (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2016)
The purpose of this study was to test the influence of the understanding of accounting system, government financial management and work environment on the performance of work units (a study in Regional Ministry Departments/ Work Units in Keerom Regency). Population of this research was the 62 respondents from finance managers in the Regional Ministry Departments/ Work Units. The sampling technique used was a non-Probability sampling in saturation sampling. Data collection was conducted through field studies and literature. A Multiple Linear Regression with the F-test and t-test was employed to analyse the data collected and test the hypotheses. The study results showed that the understanding of the government financial accounting system did not influence performance of the work units. Government financial management had no effect on the performance of the work units. Work environment influenced work units performance. Lastly, understanding government accounting system, government financial management and work environment simultaneously influenced performance of work units. Keywords : Understanding of Government Financial Accounting System, Financial Management, Work Environment, Performance of Work Units